Incorporation of some Malaysian herbal aqueous extracts as an antioxidant and antimicrobial in cakes / Izzreen Ishak - Ishak, Izzreen (2010)
This research consists of two parts. The first part is to study the antioxidative and antimicrobial properties of selected Malaysian herbal plants aqueous extracts namely curry leaves (Murraya koenigii), kesum (Polygonum minus) leaves and tenggek burung (Melicope lunu-ankenda) leaves and also to screen for phytochemical compounds present in the plants. The selected local herbs were investigated for their antioxidative activities (AOA) employing various established in vitro assays such as total phenolic content (TPC), ferric-reducing antioxidant power (FRAP), 1,1-diphenyl-2picrylhydrazyl (DPPH) free radical-scavenging ability and β-carotene bleaching assays. Oxidative stability using accelerated study in the fat system was conducted using Rancimat method. The identification of flavonoids in plant extracts also was carried out by using High Performance Liquid Chromatography (HPLC).